Perilaku Kerja Inovatif Karyawan Gen Z: Perbandingan pada Perusahaan yang menerapkan Pengaturan Kerja Fleksibel dengan yang menerapkan WFO - Widiaristi, Monica Sekar; Arum Etikariena (Fakultas Psikologi Universitas YARSI, 2024)
Gen Z employees are required to have innovative work behavior in order to increase the company's competitiveness. An organizational policies that plays a role in increasing innovative work behavior and is in accordance with the characteristics of Gen Z is flexible work arrangements. In this study, researchers want to see the relationship between flexible work arrangements and innovative work behavior in Gen Z employees who worked flexibly (WFA and hybrid). Researchers also wanted to see differences in innovative work behavior between Gen Z employees who worked flexibly and those who worked from office. Participants are 217 people aged 18-28 years old, currently working on a WFO/WFA/hybrid basis, and domiciled in Indonesia. Innovative work behavior variables are measured using the Innovative Behavior Scale and flexible work setting variables are measured using the Flexible Work Options Questionnaire (FWOQ). The results of the bootstrap analysis (N = 1000) show that flexible work arrangements can positively and significantly predict innovative work behavior (???? = 0.23, p = 0.02). Flexible work arrangements can explain 5.7% of the variance in innovative work behavior. The results of the analysis also show differences in innovative work behavior between Gen Z employees who work flexibly (M = 38.58, SD = 7.84) and Gen Z employees who work from offices (M = 33.85, SD = 9.60), statistically significant, t(215) = 3.88, p = 0.00. This research suggests companies to start implementing more flexible working arrangements so that employees feel comfortable and motivated to come up with innovative ideas.